1997
DOI: 10.2166/wst.1997.0764
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Cryptosporidium spp oocysts and Giardia spp cysts in sewage influents and effluents from treatment plants in England

Abstract: Cryptosporidium parvum and Giardia duodenalis can cause severe diarrhoea in infected individuals and their transmissive stages, oocysts and cysts, are voided in large numbers with the faeces of infected hosts. Contaminated sewage effluents are recognised as a potential source of waterborne (oo)cysts. In this investigation methods optimised for the recovery of both from a range of wastewaters were used to determine the occurrence of these organisms in influents, effluents and sludges from seven sewage treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
37
2
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 0 publications
8
37
2
6
Order By: Relevance
“…In mainland Spain a similar prevalence was found by Montemayor et al (2005). In other European countries fewer samples presented oocysts, such as UK (Bukhari et al 1997) with the 63.3% of raw sewage were positive. However, the data on the annual occurrence of Cryptosporidium sp.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…In mainland Spain a similar prevalence was found by Montemayor et al (2005). In other European countries fewer samples presented oocysts, such as UK (Bukhari et al 1997) with the 63.3% of raw sewage were positive. However, the data on the annual occurrence of Cryptosporidium sp.…”
Section: Resultssupporting
confidence: 74%
“…Molecular studies have shown that the majority of human cases are caused by C. hominis and C. parvum (Anonymous 2000, McLauchlin et al 2000. The oocysts of this parasite can be readily found in sludge, raw sewage, sewage effluents, drinking water and recreational waters (Bukhari et al 1997, Fayer et al 2000, Robertson et al 2000, Caccib et al 2003, and may represent a public health risk in developed and developing countries (LeChevalier et al 1991a, b).…”
Section: Introductionmentioning
confidence: 99%
“…1, an increase in Giardia cysts was observed three times during the purification process in the plants. As Giardia does not reproduce outside the host, this was probably due to the fact that the aggregated protozoa desegregated before sedimentation, thus increasing the concentration of free parasites in the sample, as also observed by other authors (6).…”
Section: Vol 69 2003 Giardia Cysts In Wastewater Treatment Plants 3395supporting
confidence: 70%
“…The growing interest also seems to be due to the potential cost recovery through the use of duckweed as animal feed (13,35). However, sewage water recycling may constitute a health hazard, since sewage waters are known to be potential reservoirs of pathogenic and/or drug-resistant bacteria and other pathogenic organisms (5,28) that may persist in the sewage treatment system, be recycled through the reuse of treated sewage water, and possibly spread to humans through the food chain (23,40).…”
mentioning
confidence: 99%